Is information transparency important for funders? A case study of sharia P2P lending companies in Indonesia - Yuri Oktaviani; Miranti Kartika Dewi (Universitas Muhammadiyah Yogyakarta, Indonesia, 2023)
Research aims: This study explores the importance of information transparency for funders as parties who provide funding to borrowers' projects. It also analyzes information transparency practices in sharia P2P lending.Design/Methodology/Approach: The study used a qualitative case study, focusing on three sharia P2P lending companies in Indonesia. Data were collected through interviews with parties from three sharia P2P lending companies and 11 funders.Research findings: It was found that information transparency is important for funders, increasing their confidence to invest. In addition, based on multiple agency theory, there is information asymmetry between funders and sharia P2P lending borrowers, which can be reduced by information transparency measures from funders, sharia P2P lending, and borrowers based on cost-benefit considerations. Theoretical contribution/Originality: This research explores the application of information transparency in sharia P2P lending companies, which, as far as researchers are concerned, has not been raised in previous studies. In addition, the study builds a conceptual framework of information transparency in sharia P2P lending companies based on multiple agency theory. Practitioner implication: The research has implications for applying information transparency in sharia P2P lending, which can improve information updates and communication from sharia P2P lending to its funders.Research limitation/Implication: The study only focused on three out of the seven sharia P2P lending in Indonesia. Therefore, the differences in business, focus, and other characteristics of the remaining four were not considered.